The Relationship between Parenting Style and Nutritional Intake with Children's Language Development - Nor Mai Leza; Adi Nugroho; Triawanti Triawanti (Indonesian Journal of Global Health Research, 2026)
Language development is a fundamental aspect of early childhood's golden period, influenced by environmental factors, namely parenting patterns and biological foundations through nutritional intake. This literature review aims to analyze the relationship between parenting patterns and nutritional intake and children's language development. The data used are secondary data in the form of articles from PubMed, Science Direct, and Google Scholar. Researchers used 21 national and international research articles published between 2020 and 2025. The inclusion criteria for this study were: 1) primary research articles published between 2020 and 2025; 2) article topics aligned with the research objectives; and 3) articles from accredited national full access journals and reputable international journals. The synthesis of results indicates that parenting patterns that provide positive verbal stimulation and interaction, as well as regulating gadget use, can improve children's receptive and expressive language skills. Conversely, excessive gadget use without parental supervision can increase the risk of language delay. From a nutritional perspective, stunting and micronutrient deficiencies (especially iron and zinc) contribute to impaired cognitive function and attention, which impact children's language acquisition. In conclusion, children's language development is influenced by a combination of parenting patterns and nutritional intake, with good parenting patterns and balanced nutritional intake being key components in supporting optimal language development.